Canibalism in the larval instars of Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae): temperature and food quantity - Lorena Contarini Machado; Hugo José Gonçalves dos Santos Junior; Carlos Eduardo Costa Paiva; Beatriz Almeida dos Santos; Laura Vaillant Ribeiro Mauri; Julianne Almeida Rodrigues; Carolina de Oliveira Soares; Hugo Bolsoni Zago (Acta Scientiarum. Biological Sciences, 2022)
Cannibalism is a frequent behavior in Spodoptera frugiperda (J. E. Smith, 1797) larvae either in the field or in a laboratory. The purpose of this work was to investigate the factors temperature and food quantity on the cannibal behavior in instars of this insect under laboratory conditions. The neonates were conditioned at temperatures of 22, 25, 28 and 31 ± 1°C until they reached the 3rd, 4th, and 5th instar. The number of 20 larvae were transferred to different gerbox® with the amount of food varying from 0, 5, 10, 15, and 20 g of artificial diet. Cannibalism was evaluated after 72 hours. In all the instars evaluated, the larvae showed cannibalistic behavior as a function of temperature and amount of food. The amount of 15 g of artificial diet is sufficient to feed the 3rd and 4th instar larval for 72h, regardless of temperature. For the 5th instar this amount is 10 g.